The effect of Nickel Oxide (NiO) compositions in consolidation of Silica-Nickel Oxide (SiO²-NiO) foams using replication method / P.S. Abdul Rahim ... [et al.] - Abdul Rahim, P.S; Shamsudin, M.S.; M., Rizamarhaiza; Nazaruddin, N.A. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Ceramic foams contribute to wide range of engineering application such as filter, thermal insulator, biomedical implant and catalytic reaction. There are many methods can be used found to be fabricating ceramic foams, however, replication method is the most effective method in producing ceramic foams. Fabrication of Silicon Dioxide (SiO2) foam with the addition of Nickel Oxide (NiO) by using replication method at different compositions was studied. The composition of SiO2 applied was at 55 wt. % while the compositions of NiO were 0, 5 and 7 wt. %. Polyethylene Glycol (PEG) and Carboxymethyl Cellulose (CMC) were used as binders while Polyurethane (PU) foam in cylindrical form was applied as space holder. Upon impregnation of the PU foams with SiO2-NiO slurries, drying process was performed at 100℃ for 24 hours. Then, the sample was further sintered at 600℃ for an hour and 1300℃ for two hours with heating rate at 2℃/min and natural cooling in the furnace.